The molecular structure of mammalian primary cilia revealed by cryo-electron tomography - Kiesel, Petra; Alvarez Viar, Gonzalo; Tsoy, Nikolai; Maraspini, Riccardo; Gorilak, Peter; Varga, Vladimir; Honigmann, Alf; Pigino, Gaia (Nature structural & molecular biology, 2020)
Primary cilia are microtubule-based organelles that are important for signaling and sensing in eukaryotic cells. Unlike the thoroughly studied motile cilia, the three-dimensional architecture and molecular composition of primary cilia are largely unexplored. Yet, studying these aspects is necessary to understand how primary cilia function in health and disease. We developed an enabling method for investigating the structure of primary cilia isolated from MDCK-II cells at molecular resolution by cryo-electron tomography. We show that the textbook '9 + 0' arrangement of microtubule doublets is only present at the primary cilium base. A few microns out, the architecture changes into an unstructured bundle of EB1-decorated microtubules and actin filaments, putting an end to a long debate on the presence or absence of actin filaments in primary cilia. Our work provides a plethora of insights into the molecular structure of primary cilia and offers a methodological framework to study these important organelles.
Keywords: Chlamydomonas; psi; cilie; exprese genu; Humans; Actin Cytoskeleton; Dogs; Gene Expression; Electron Microscope Tomography; Microtubules; lidé; tomografie elektronová; zvířata; Cilia; mikrotubuly; buňky MDCK; Madin Darby Canine Kidney Cells; Microtubule-Associated Proteins; proteiny asociované s mikrotubuly; Animals; Cell Culture Techniques; elektronová kryomikroskopie; mikrofilamenta; Cryoelectron Microscopy; buněčné kultury